2011
DOI: 10.1021/bi2002373
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics and Solvent Effects on Substrate and Cofactor Binding in Escherichia coli Chromosomal Dihydrofolate Reductase

Abstract: Chromosomal dihydrofolate reductase from Escherichia coli catalyzes the reduction of dihydrofolate to tetrahydrofolate using NADPH as a cofactor. The thermodynamics of ligand binding were examined using an isothermal titration calorimetry approach. Using buffers with different heats of ionization, zero to a small, fractional proton release was observed for dihydrofolate binding, while a proton was released upon NADP(+) binding. The role of water in binding was additionally monitored using a number of different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
74
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(85 citation statements)
references
References 102 publications
11
74
0
Order By: Relevance
“…A similar set of results was observed. Binding of DHF to EcDHFR, as measured by ITC, was weaker in the presence of osmolytes compared to buffer alone, while NADPH binding was strengthened by addition of osmolytes [54]. Stopped-flow studies provided further insight into how osmolytes affected ligand binding.…”
Section: 1 Osmotic Stress Experiments Probe the Role Of Watermentioning
confidence: 99%
See 1 more Smart Citation
“…A similar set of results was observed. Binding of DHF to EcDHFR, as measured by ITC, was weaker in the presence of osmolytes compared to buffer alone, while NADPH binding was strengthened by addition of osmolytes [54]. Stopped-flow studies provided further insight into how osmolytes affected ligand binding.…”
Section: 1 Osmotic Stress Experiments Probe the Role Of Watermentioning
confidence: 99%
“…Typically, a structural technique, such as circular dichroism, is used to monitor any changes in the secondary structure of the biomacromolecule [54, 55, 62]. If there are changes in the biomacromolecule structure, then these structural changes will also affect the ITC results.…”
Section: 1 Conclusionmentioning
confidence: 99%
“…We solved for the free enzyme and ligand concentrations using thermodynamic equilibrium constants (Table S1) determined previously by isothermal titration calorimetry (ITC) for the interaction of DHFR with folate and DHFR with NADP + . 39 We were unable to find the necessary equilibrium constants for the binding of folate to DHFR·NADP + in the literature; therefore, we determined this value ourselves using ITC (Figure S2 and Table S1). …”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have found that the in vitro addition of osmolytes to three different protein scaffolds that catalyze the dihydrofolate reductase (DHFR) reaction results in tighter binding of cofactor NADPH (8)(9)(10). Addition of osmolytes lowers the water activity of a solution; dehydration typically leads to tighter ligand binding, as less solvent needs to be removed to form a complex.…”
mentioning
confidence: 99%
“…Addition of osmolytes lowers the water activity of a solution; dehydration typically leads to tighter ligand binding, as less solvent needs to be removed to form a complex. In contrast, binding of DHF "breaks the rules," as weaker binding upon osmolyte addition is observed in these three different proteins (8)(9)(10). To model this behavior, we proposed that osmolytes weakly associate with DHF.…”
mentioning
confidence: 99%